Aesthetic Value Assessment Coupled with Landscape Character Assessment for Hengshan Mountain Scenic Area - Renjing ZHAO; Bingtai XING; Yuqian WANG (Fengjing Yuanlin, 2025)
ObjectiveIn order to align with international standards and promote the construction of a global ecological civilization while ensuring the distinctive protection of China’s natural and cultural resources, China has gradually clarified a plan for deepening the reform of a protected area system mainly composed of national parks. Scenic and historic areas encompass natural and cultural landscapes with unique Chinese characteristics within the national territory of China, and their management system has been continuously improved over the past forty years of development. The scattered layout of multiple areas in Hengshan Mountain has led to an imbalance in the protection, control, inheritance, and development of scenic resources in each area. In the context of the reconstruction of the protected area system, how to respond to the protection and control demands of scenic and historic areas remains an issue in urgent need of exploration.In the context of the new era, this research attempts to, by coupling landscape character assessment with aesthetic value assessment, explore the management and protection of scenic and historic areas, and explain the internal temporal and spatial order and correlation reflected in various types of landscapes, so as to help reduce the fragmentation and incompleteness of landscapes, expand the protection boundaries, connotation boundaries, and time boundaries of landscape resources. The research can assist in delineating the key protection areas of scenic and historic areas guided by aesthetic values, thereby achieving overall protection from point scenery to area scenery. The research can also provide new perspectives for solving a series of problems in the process of integrating and optimizing scenic spots, such as the demand for sightseeing activities, conflicts in urban development, and inheritance of ecological and cultural values, and be able to improve the international heritage aesthetic assessment system from a Chinese perspective.MethodsBased on the guidance ideas, evaluation methods, technical platforms, and conclusion descriptions of relevant landscape character assessment at home and abroad, and on the basis of determining the scope of the research object, a research framework for aesthetic value assessment coupled with landscape character assessment for Hengshan Mountain Scenic Area is constructed through the combination of elbow method, K-means, entropy weight method, and TOPSIS method, which includes two stages: landscape character assessment and aesthetic value assessment. The stage of landscape character assessment mainly includes three steps: 1) Screening and classified identification of landscape character elements; 2) classification and mapping of landscape character; 3) translation and description of landscape character types. The stage of aesthetic value assessment mainly includes two steps: 1) Screening of aesthetic value assessment indicators; 2) aesthetic value grading and regional identification. Taking the Hengshan Mountain Sceinc Area, which has a scattered layout of multiple protected areas, as an example, this research conducts an aesthetic value assessment practice couple with the identification of landscape characters.ResultsThis research screens and classifies the landscape character elements of the Hengshan Mountain Sceinc Area, and uses ArcGIS 10.6 to encode and visualize the classified elements, with the spatial area ratio and distribution characteristics of each element being identified. By virtue of the ArcGIS 10.6 spatial analysis tool, 14,738 150 m × 150 m cells are constructed within the research scope of Hengshan Mountain Sceinc Area, and a gridded geographic information database of various elements is established. Additionally, the research identifies 24 types and zones of landscape characters in Hengshan Mountain Sceinc Area, screens and classifies the aesthetic value assessment indicators of Hengshan Mountain Sceinc Area, and constructs a grid database for each assessment element. The research also conducts a 5-level assessment, classification and zoning of aesthetic value. It is found that within the core area and peripheral protected areas of Hengshan Mountain Sceinc Area, the distribution ratio of aesthetic value zones at all levels is relatively balanced. The distribution characteristics of different levels of aesthetic value zones and the types of landscape characters covered are analyzed, and the main factors affecting aesthetic value are identified based on the types of landscape characters included in various levels of aesthetic value zones, including cultural scenic spots, vegetation coverage index, and water.ConclusionThe research on aesthetic value assessment coupled with landscape character assessment offers a possibility of determining the protection intensity and utilization methods of scenic and historic areas based on the difference in aesthetic value, providing a more macro perspective for the protection of scenic and historic areas. The research expands the scope of assessment objects, screens assessment elements that reflect the historical and cultural characteristics of scenic and historic areas, and balances the subjectivity and objectivity of assessment methods. The assessment results illustrate the landscape character types and aesthetic value features of scenic and historic areas in the form of a “picture”, which can effectively connect with higher-level planning, promote the balanced development of various areas and types of landscape resources, and guide the resilient protection and sustainable development of scenic and historic areas. Under the research idea that resource characteristics, control objectives, and value orientation jointly determine protection norms, this research focuses on explaining the feasibility of evaluating the overall, refined, and targeted protection of scenic and historic areas, as well as the necessity of balancing the protection and utilization of scenic and historic areas through assessment and coordination under the management concept of “maximizing the scope of protection”.